Pengaruh Corporate Social Responsibility (CSR) Disclosure terhadap Profitabilitas Perusahaan - Siti Wulandari (Jurnal Ekonomi Akuntansi dan Manajemen, 2020)
The purpose of this study is to examine and analyze the effect of Corporate Social Responsibility Disclosure on company profitability in plantation subsector companies that listed on the Indonesia Stock Exchange on 2016-2018. This research is a type of quantitative research that using secondary data, namely the annual report of the plantation subsector company 2016-2018. Independent variable that used in this research is CSR Disclosure which is measured using CSRDI and the dependent variable is company profitability which is proxied by the ratio of ROA, ROE, and NPM. The results show that CSR Disclosure have the positive and significant effect on ROA with a significance value of 0.012, ROE of 0.035, and NPM of 0.028. The results of this study indicate that empirically disclosing CSR activities in plantation subsector companies will increase company profitability. Keywords: CSR Disclosure, NPM, ROA, ROE.